2014
DOI: 10.1038/ejcn.2014.190
|View full text |Cite
|
Sign up to set email alerts
|

Reference amounts utilised in front of package nutrition labelling; impact on product healthfulness evaluations

Abstract: BACKGROUND/OBJECTIVES:The research question addressed in this paper is how different reference amounts utilised in front of package nutrition labelling influence evaluation of product healthfulness. SUBJECTS/METHODS: A total of 13 117 participants from six European countries (Germany, UK, Spain, France, Poland and Sweden) were recruited via online panels. A mixed between/within-subject factorial design was employed with food (biscuits, sandwiches, yogurts), healthfulness and presence of Guideline Daily Amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…This is in line with the sample size recommendations for discrete choice tasks [53]. Previous studies have reported small to medium effect sizes for the FoPL x healthiness interaction on perceived healthiness (η p 2 = 0.008 [54], 0.01 [55]; d = 0.5 [56]). Thus, a large sample will be employed to ensure that even small effects are detected.…”
Section: Participantssupporting
confidence: 89%
“…This is in line with the sample size recommendations for discrete choice tasks [53]. Previous studies have reported small to medium effect sizes for the FoPL x healthiness interaction on perceived healthiness (η p 2 = 0.008 [54], 0.01 [55]; d = 0.5 [56]). Thus, a large sample will be employed to ensure that even small effects are detected.…”
Section: Participantssupporting
confidence: 89%
“…Health Star Rating system, Nutri-Score, the Warning symbols), or have explored the effectiveness of these FoPLs across different countries. The literature suggests the potential influence of sociocultural contexts on understanding and use of FoPLs [13][14][15], making international comparisons important when attempting to identify FoPLs that would be appropriate for cross-country application. The present study compares the performance of the five FoPLs in terms of objective understanding of nutritional quality and food choices among consumers in 12 European countries participating in the FOP-ICE (Front-Of-Pack International Comparative Experimental) study [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the size of the differences detected in this study may be considered small (e.g., a difference of 0.1 on a 5 point scale), this is to be expected given that factors such as taste, price and convenience often have a greater impact on product evaluations than healthiness [70], and previous studies also generally report small changes [48,71,72]. In these experimental studies, exposure to the labelling intervention is relatively brief.…”
Section: Discussionmentioning
confidence: 82%